Nitrogen-rich tetracyclic-based heterocyclic energetic materials - Jie Tang; Hong-wei Yang; Guang-bin Cheng (Energetic Materials Frontiers, 2023)
This review provides numerous studies on nitrogen-rich tetracyclic-based heterocyclic energetic materials including oxadiazole, tetrazole, triazole, pyrazole, imidazole and tetrazine. The article mainly describes the construction method of energetic skeleton, explosive modification, and properties of tetracyclic energetic materials. The structure-property relationship was obtained by comparing the properties of a series of nitrogen-rich energetic materials. Finally, authors summarize the synthesis laws of energetic skeletons, which provides reference for the development of energetic materials in the future.